A Tripartite Evolutionary Game Analysis of Enterprises’ Behaviour in the Platform Ecosystem - Ying Han (Discrete Dynamics in Nature and Society)
With the rapid progress of digital technology and new business models’ development, the platform ecosystem has not only penetrated every sector in society but also revealed various problems. Platform governance researchers have highlighted its significance, but failed to adequately consider ecosystem participants’ behaviour. This paper aims to explore platform governance’s effects on enterprises’ behaviour in a multiorganisational platform ecosystem context. The tripartite evolutionary game is chosen to construct a mathematical model that integrates the government, platform organisation, and internal enterprises to analyse formal and informal governance’s influence on enterprises’ behaviour in the platform ecosystem. It was discovered that both formal and informal governance can decrease internal enterprises’ opportunistic behaviours. Furthermore, formal governance has stronger effects than informal governance, although informal governance’s effects are more stable. Additionally, self-organisation in the platform ecosystem is another important area of focus. This paper enriches an understanding of platform ecosystems while formulating insights relevant in using platform governance to develop small and medium-sized enterprises.